2014
DOI: 10.1182/blood.v124.21.1464.1464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eltrombopag on Platelet Response and Safety Results in Chinese Adults with Chronic ITP-Primary Result of a Phase III Study

Abstract: INTRODUCTION: Eltrombopag (PROMACTA®/REVOLADE®; GlaxoSmithKline) is a non peptide, oral thrombopoietin receptor agonist which promotes the differentiation and proliferation of megakaryocytes and increases platelet counts. In previous studies, East Asians ITP subjects had an approximately 1.85 fold higher plasma eltrombopag AUC (0-τ) and 1.6 fold higher plasma eltrombopag Cmax than non-East Asian ITP subjects who were predominantly Caucasian. An initial dose of 25mg once daily has not been studied in a randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Among the remaining non‐surgical therapies, we identified 12 prospective RCTs with a placebo or SOC arm evaluating the safety and efficacy of eltrombopag (5 studies), rituximab (2 studies), or romiplostim (5 studies, with one publication reporting on two studies conducted in parallel). (No head‐to‐head RCTs directly comparing one second‐line therapy of interest to another were found.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the remaining non‐surgical therapies, we identified 12 prospective RCTs with a placebo or SOC arm evaluating the safety and efficacy of eltrombopag (5 studies), rituximab (2 studies), or romiplostim (5 studies, with one publication reporting on two studies conducted in parallel). (No head‐to‐head RCTs directly comparing one second‐line therapy of interest to another were found.)…”
Section: Resultsmentioning
confidence: 99%
“…These studies are summarized in more detail in Table , and study‐specific definitions of the outcomes/endpoints common to at least two of the studies are provided in Table . Two studies were prospective phase 2, placebo‐controlled RCTs (1 eltrombopag and 1 romiplostim); one was a prospective SOC‐controlled, open label RCT (romiplostim); one was a prospective placebo‐controlled pilot RCT (rituximab); and the remaining eight studies were prospective phase 3, placebo‐controlled RCTs (4 eltrombopag, 1 rituximab, and 3 romiplostim).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Randomized controlled studies showed that eltrombopag achieved early platelet response in 70–80% of the patients and a remission rate of 20–30% [ 119 , 120 , 121 , 122 ]. In an open-label extension study, 85% of the patients achieved a platelet response, and 52% of them had a continuous response of 25 weeks or longer [ 123 ].…”
Section: Treatment Of Itpmentioning
confidence: 99%